2018
DOI: 10.1088/1361-6528/aab4d3
|View full text |Cite
|
Sign up to set email alerts
|

Soft-type trap-induced degradation of MoS2 field effect transistors

Abstract: The practical applicability of electronic devices is largely determined by the reliability of field effect transistors (FETs), necessitating constant searches for new and better-performing semiconductors. We investigated the stress-induced degradation of MoS multilayer FETs, revealing a steady decrease of drain current by 56% from the initial value after 30 min. The drain current recovers to the initial state when the transistor is completely turned off, indicating the roles of soft-traps in the apparent degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We employ this data processing algorithm for a number of ΔI(t) data obtained from various 2D material based FETs which have been fabricated and analyzed under various experimental conditions such as different gate dielectrics 11,13,34,35 , temperatures 11,34,36 , channel materials 10,11,13,34,35,[37][38][39] , chemical/electron beam doping 40,41 , and source/drain contact metals 11,34 (see Fig. 1b).…”
Section: Workflow For Audio and Current Signal Classificationmentioning
confidence: 99%
“…We employ this data processing algorithm for a number of ΔI(t) data obtained from various 2D material based FETs which have been fabricated and analyzed under various experimental conditions such as different gate dielectrics 11,13,34,35 , temperatures 11,34,36 , channel materials 10,11,13,34,35,[37][38][39] , chemical/electron beam doping 40,41 , and source/drain contact metals 11,34 (see Fig. 1b).…”
Section: Workflow For Audio and Current Signal Classificationmentioning
confidence: 99%
“…Schottky barriers inevitably form at the semiconductor TMD–metal junctions, which can greatly degrade device performance . The Schottky barriers are not simply determined by the difference between the conduction band minimum or the valance band maximum of the TMD and the work function of the metal, but forming an Ohmic contact is difficult because Fermi level pinning occurs. Research studies on the interface between the TMD and the metal and the interface between the TMD and the gate dielectric have been actively performed. Recently, studies have been conducted to improve the interface property by inserting a dangling bond-free hexagonal BN ( h -BN) between the TMD and the gate dielectric or between the TMD and the metal contact . In addition, some studies have shown that thermal annealing alleviated Fermi level pinning by improving interfacial properties. ,,,, …”
Section: Introductionmentioning
confidence: 99%